2011
DOI: 10.1097/mpg.0b013e3181fa06f3
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pediatric Rumination Syndrome: Successful Interdisciplinary Inpatient Management

Abstract: This treatment protocol could benefit pediatric gastroenterologists, pediatricians, and child psychologists in managing both standard and severe cases of rumination syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…However, DiLorenzo et al have shown that, when psychiatric disorders are present, it is helpful to address these issues for successful treatment, indicating a substantial role of the psychiatric disorder in rumination syndrome. 29 …”
Section: Discussionmentioning
confidence: 99%
“…However, DiLorenzo et al have shown that, when psychiatric disorders are present, it is helpful to address these issues for successful treatment, indicating a substantial role of the psychiatric disorder in rumination syndrome. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Even though, rumination has been reported in males [15,16], the majority of patients in previous hospital based studies and case reports on this disorder were females [3,17-19]. In a previous review of 147 children with rumination syndrome, 68% were females [4].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of rumination disorder is unknown. In part, this is due to significant variability in use of diagnostic terms (eg, regurgitation disorder, 29 rumination syndrome 30 ) and classification schemes 31 to describe essentially similar presentations. Additionally, a clear distinction is not always made between rumination or regurgitation as…”
Section: Prevalence Of Rumination Disordermentioning
confidence: 99%